Attitudes and intentional reactions towards mariculture development –local residents' perspective. (15th May 2019) - Armbrecht, John; Skallerud, Kåre
Highlights: Environmental concerns and economic opportunities affect mariculture attitudes. Tourism attitudes have no effect on mariculture attitudes among locals. Mariculture attitudes have an effect on intentional reactions among locals.